1986
DOI: 10.1007/bf00710766
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric analysis of osteoclastic bone resorption in metastatic bone disease from various primary malignomas

Abstract: The present study deals with qualitative und quantitative analysis of osteoclastic bone resorption in metastatic bone disease. 267 cases were examined histomorphologically and divided into three developmental stages. In the first 'phase of early appearance' no bone resorption takes place. The stimulation of osteoclastic resorption in the surroundings of tumour tissue is typical in the second 'phase of interaction'. Pressure atrophy, aseptic necrosis and osteolysis by the tumour cells themselves are other mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…It has been suggested, on the basis of data from several experimental models and from analysis of human biopsy specimens, that osteoclasts are responsible for bone resorption at sites of osteolytic tumors (1,(3)(4)(5)(6)8,10,14,17,20,22,27). Our findings advance this concept one step further by demonstrating that osteoclasts are required for 2472 tumor-induced osteolysis to occur.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It has been suggested, on the basis of data from several experimental models and from analysis of human biopsy specimens, that osteoclasts are responsible for bone resorption at sites of osteolytic tumors (1,(3)(4)(5)(6)8,10,14,17,20,22,27). Our findings advance this concept one step further by demonstrating that osteoclasts are required for 2472 tumor-induced osteolysis to occur.…”
Section: Discussionsupporting
confidence: 59%
“…Descriptions from zn vivo expcriments with both tumors revealed that bone was destroyed at sites of tumor and that no osteoclasts were present. These observations suggest that osteoclasts may not be involved in the pathogenesis of tumor osteolysis (15J9): however, the possibility exists that osteoclasts were present before the point at which the tumor-bearing bone was collected (14). It therefore becomes important to determine when tumor osteolysis is actually occurring in the experimental model under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could suggest that large giant multinucleated osteoclasts are able to retain some residual bone resorptive activity as an indication of partly-reduced sensitivity. Large multinucleated osteoclasts are also often seen in the context of cancer bone metastases [ 111 , 112 ]. Precisely in cancer, suppression of bone resorption is important to treat the bone disease.…”
Section: Implications For Physiology and Pathologymentioning
confidence: 99%
“…Some disagreement exists as to whether the giant cells within the tumor are actually osteoclasts that resorb bone underlying the GCTB or whether the osteoclasts seen resorbing the bone arrived by chemotaxis [11,12]. Cytokines produced in metastases to bone are known to recruit osteoclasts [13]. In the electron microscope, intervening cells, membranes, and fibrous stromal tissue usually can be seen between the GCTB and active osteoclasts on the bone [14].…”
mentioning
confidence: 98%